Synthesis and H2S Gas Sensing Characteritics of Nanostructured V2O5 - Do, Quang Dat; Nguyen, Thi Lan Phuong; Vo, Thi Lan Phuong; Pham, Thi Nga; Lai, Van Duy; Lam, Van Nang; Nguyen, Van Duy; Nguyen, Duc Hoa (JST: Engineering And Technology For Sustainable Development, 2021)
In this study, V2O5 nanomaterials were successfully synthesized by a facile hydrothermal method and tested for application in preparing toxic H2S gas sensor. SEM image shows that the material has the shape of nanoplates with different sizes ranging from 100 to 500 nm. The XRD pattern shows that the material has a single phase of Orthorhombic crystal of V2O5. The results of the gas sensitivity survey show that the material good respond to H2S at low concentrations (2.5-20 ppm) with relatively fast response and recovery time. This study demonstrates the potential of application of V2O5 material in H2S gas sensors.